Nutrition Consultation and Egg White Extras at the Knowledge and Albumin Level Pulmonary Tuberculosis (Tb) Patients in the Irna Room, RSUD Dr. R. Soedarsono, Pasuruan City - Putri Merina; Nur Rahman; Sutomo Rum Teguh Kaswari (Pusat Unggulan IPTEK POLTEKKES KEMENKES Malang, 2022)
Tuberculosis is a lung infection characterized by pulmonary infiltrates and caseous granuloma formation, fibrosis and cavity. Extra egg white administration can increase serum albumin levels by an average of 1.13 g by dL. Nutrition counseling is very important given to increase knowledge and change attitudes or behaviors of pulmonary TB patients. The purpose of this study was to determine the effect of giving nutritional counseling and extra egg white to the knowledge and levels of albumin in pulmonary tuberculosis patients in the IRNA room of the RSUD dr. R. Soedarsono, Pasuruan city. This research is a quasi experimental study with the research design used is the Desaign Group Pretest-Posttest Control. From the Wilcoxon statistical test the Asymp. Sig value is obtained. 2-tailed of 0.001 smaller than 0.05, so Ho is accepted as meaning there are differences in the level of knowledge before and after obtaining nutritional counseling and the value of Asymp.Sig is also obtained. 2-tailed of 0.001 smaller than 0.05, then Ho is accepted by means of differences in albumin levels in the treatment group. There is an effect of nutritional counseling on the knowledge of control and treatment respondents before and after being given nutritional counseling. There was a difference or increase in pre and post albumin levels given extra white egg in the treatment group with an average increase of 0.21 g by dl.